A new two-phase flow model based on coupling of the depth-integrated continuum method and discrete element method. (January 2021) - An, Huicong; Ouyang, Chaojun; Wang, Dongpo
Abstract: The evolution of the volume fraction of solid phase, basal entrainment and interactions between the solid and fluid phase have significant impacts on rheological behavior, dynamic characteristics, and volume amplification in some earth-surface flows, including debris flows, hyper-concentration flows, dam-break flows. In this study, we propose a new two-phase flow dynamic model based on coupling of the depth-integrated continuum method and discrete element method (DEM). The fluid phase is computed by the depth-integrated continuum method, while the solid phase is modeled by the discrete element method. The data exchange between the two phases is efficiently handled by setting shared variables between the separate computational frameworks. The basal topography is simultaneously updated by numerically monitoring when solid particles are entrained into the fluid or deposited from the fluid. The current method provides a guiding solution for the common need to couple computations among multiple models. We examine several computational cases and compare the results with the theoretical solution and the experimental results. We conclude that the computational framework has unique advantages, placing it in a position to solve some ticklish issues in the field of fluid-solid interactions. Highlights: A new fast-computing two-phase model by depth-integrated continuum and DEM is proposed A new erosion rate computational model directly from discrete particles is proposed. Several computational cases compared with experiments are well calculated.